Social Classification Reflected in Anne Bronte's Agnes Grey (1847): Marxist Theory - Darussalam, Risal Yaniardi; , Dr. Phil. Dewi Candraningrum, S.Pd, M.Ed (2016)
This study is aimed to reveal the social classification in Agnes Grey (1847) novel by Anne Bronte. Agnes Grey (1847) novel is analyzed by using Marxist approach. The analysis is done by determining two objects: the first is analyzing the novel based on the structural elements, and the second is analyzing the problem of social classification by using Marxist approach. This research is a descriptive qualitative research. There are two types of data sources. The source of primary data is Anne Bronte's Agnes Grey (1847) novel. The secondary data sources are from books, biography of the author, journals, and internet sources related to the study. The two kinds of data collected through library research and analyzed with descriptive analysis. Based on the research, the researcher draws the following conclusions. The first, the structural element of the novel described the character and characterization, setting of place and time, plot, point of view, and theme. It shapes into one unity in a novel story. The second, based on Marxist approach in dialectical, historical, class struggle, alienation, revolution and the social discrimination was revealed with other descriptions of Marxist the major character reflected in Agnes Grey (1847) novel.